Intergroup aggression in meerkats. Issue 1917 (18th December 2019) - Dyble, Mark; Houslay, Thomas M.; Manser, Marta B.; Clutton-Brock, Tim
Abstract : Violent conflicts between groups have been observed among many species of group living mammals and can have important fitness consequences, with individuals being injured or killed and with losing groups surrendering territory. Here, we explore between-group conflict among meerkats ( Suricata suricatta ), a highly social and cooperatively breeding mongoose. We show that interactions between meerkat groups are frequently aggressive and sometimes escalate to fighting and lethal violence and that these interactions have consequences for group territories, with losing groups moving to sleeping burrows closer to the centre of their territories following an intergroup interaction and with winning groups moving further away. We find that larger groups and groups with pups are significantly more likely to win contests, but that the location of the contest, adult sex ratio, and mean within-group genetic relatedness do not predict contest outcome. Our results suggest that intergroup competition may be a major selective force among meerkats, reinforcing the success of large groups and increasing the vulnerability of small groups to extinction. The presence of both within-group cooperation and between-group hostility in meerkats make them a valuable point of comparison in attempts to understand the ecological and evolutionary roots of human warfare.